Retention of Proto-Austronesian vowels in the Karo language: A comparative historical linguistics study - Dardanila Dardanila; Erik D Siregar; Sholihatul Hamidah Daulay (Universitas Syiah Kuala, 2025)
The purpose of this research is to analyze the inheritance of vowels in the Karo language or Bahasa Karo (hereafter, BK) from Proto-Austronesian (PAN), and BK words that show the retention or inheritance of certain vowels, such as /a/, /i/, /u/, and //. The method involved comparing the phonological elements of BK with the equivalent elements in PAN by using the theory of comparative historical linguistics, including searching for inherited vowels in the penultimate and ultimate positions and observing the retention patterns that occur. The data were derived from 200 Swadesh words and three interviewers. Vocal retention occurs more frequently in the penultimate position than in the ultimate position. This shows how phonological positions affect vowel stability during language transition. These findings conclude that certain phonological components, particularly vowels, have a greater tendency to persist in specific environments. BK has preserved a significant portion of the original PAN vowel inventory, exhibiting less vowel reduction and merger compared to adjacent languages. The retention of vowels in BK indicates a phonological conservatism relative to the more dynamic vowel alterations observed in other Austronesian branches. This study also found a close relationship between PAN and BK in the inheritance of phonological elements of linear vocal of /a/,/i/,/u/,/e/, and one nonlinear vowel sound of /o/. Another important result is the transfer of the vowel /u/ from PAN to BK in the ultimate position shows a pattern of retention or direct inheritance.